2015
DOI: 10.4236/sgre.2015.61002
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Production from an Alkali Electrolyzer Operating with Egypt Natural Resources

Abstract: Egypt is bordered by coastal sea 2450 km, while incident solar radiation is in the order of magnitudes of 1900-2200 W/m 2 in that area of the world. The present work is aimed to assess the hydrogen production from the solar-hydrogen system composed of photovoltaic cell motivated by solar energy and supplies electricity to alkali electrolyzer. The electrolyzer uses sea and Nile water as electrolytes. Indoor tests are done to identify the optimum concentration ratio of the sea water to produce hydrogen. Experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…The proposed system comprises of seven subsystems, namely, PV panels, absorption chiller for cooling from low‐grade heat, electrolyzer, hydrogen blended HCCI engine, RO plant, biomass combustor, and organic Rankine cycle (ORC) units. Typical PV driven hydrogen production electrolyzer is selected . About 290 PV modules are utilized with the capacity of 75 W each.…”
Section: System Descriptionmentioning
confidence: 99%
See 3 more Smart Citations
“…The proposed system comprises of seven subsystems, namely, PV panels, absorption chiller for cooling from low‐grade heat, electrolyzer, hydrogen blended HCCI engine, RO plant, biomass combustor, and organic Rankine cycle (ORC) units. Typical PV driven hydrogen production electrolyzer is selected . About 290 PV modules are utilized with the capacity of 75 W each.…”
Section: System Descriptionmentioning
confidence: 99%
“…About 290 PV modules are utilized with the capacity of 75 W each. The manufacturer data about these modules can be found in Table . The heat exchanger (HE) 1 heats up the water flowing to the electrolyzer for the increased rate of hydrogen production.…”
Section: System Descriptionmentioning
confidence: 99%
See 2 more Smart Citations
“…5,6 Studies have shown that the combination of pollutant removal with simultaneous generation of hydrogen fuel during electrolysis appears to be promising. 7,8 Obtaining hydrogen through the electrolysis of water is a process of decomposing H 2 O by providing energy in the form of electricity; however, this method requires a large energy expenditure in order to perform the electrolytic decomposition of water. 9 Despite a negative energy balance, electrolysis of water is still a viable option for hydrogen gas production.…”
Section: Introductionmentioning
confidence: 99%